Technology-Based Marketing: Industrial Revolution 4.0, Needs, Challenges and Solutions for Sayurbox Companies - Galih Kusuma, Andriyan (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2024)
Revolution 4.0 is a technological development designed to increase the efficiency and effectiveness of business processes. Various leading technologies such as machine learning, cloud computing, the Internet of Things (IoT), blockchain, and various artificial intelligence have been used to support revolution 4.0. SayurBox is one of the revolutions in the agricultural industry in the 4.0 era. With this, companies can create additional value for customers and increase profits. At the same time, the marketing mix remains an integral part of technological progress. This is because the marketing mix has increased customer engagement by increasing the relevance aspect and creating additional value for market competition. With the marketing mix, companies can integrate 4.0 technologies such as artificial intelligence, augmented reality, and others to create offers that are customer- friendly, real, and sustainable. This will help companies to incorporate convenience, flexibility, and a personalized experience into their services to attract new customers and retain loyal customers.